FARMERS' PERCEPTIONS OF SMALLHOLDER OIL PALM REPLANTING IN SIMPANG KANAN DISTRICT, ACEH SINGKIL REGENCY (Case Study of Oil Palm Farmer In Lipat Kajang Village) - Ridani Ridani; Setia Budi; Irada Sinta (LPPM Universitas Malikussaleh - Indonesia, 2023)
Lipat Kajang Village is one of 25 villages in Simpang Kanan District, Aceh Singkil Regency which is the research location. This study aims to analyze farmer perceptions and analyze the relationship between farmer characteristics and farmer perceptions of oil palm rejuvenation in Simpang Kanan District, Aceh Singkil District. Farmers' perception of the source of capital/access to production facilities shows 43% that production facilities are not easy to access, the costs incurred for rejuvenating oil palm are very high showing 95% and technical rejuvenation of oil palm using the method of falling simultaneously is easy to do showing 64%. Furthermore, the relationship between farmer characteristics and farmers' perceptions of oil palm rejuvenation in Simpang Kanan District, Aceh Singkil Regency has a very strong relationship by obtaining a correlation coefficient of 0.008.